Shell growth patterns and microstructure of Arctica islandica . - Nils Höche (10204233); Eric O. Walliser (10204236); Niels J. de Winter (3358778); Rob Witbaard (549727); Bernd R. Schöne (8187015) (2021)
(A) Sketch of the left valve of a juvenile specimen. Cutting axis is indicated as orange line. (B) Radial shell section of the valve. The shell is divided into an outer shell layer (OSL; white) and inner shell layer (ISL; gray), separated by the pallial myostracum (blue line). (C) Magnified sketch of the hinge plate showing annual growth lines (dashed) and axis of maximum growth (black line with arrow). (D) Sketch of the microstructures of the ventral shell portion. The outer portion of the outer shell layer (oOSL) consists of homogeneous (HOM) microstructure, which gradually merge into crossed-acicular (CA) microstructure toward the inner portion of the outer shell layer (iOSL). Transitional fine complex crossed-lamellar (FCCL) and CA microstructures are formed in the inner shell layer (ISL). Annual growth lines (GL) and pallial myostracum (My.) consist of irregular simple prismatic (ISP) microstructure. (E) Sketch of the microstructures in the hinge plate. Growth increments and lines are composed of CA and ISP microstructures, respectively. Dashed black lines represent annual growth lines. Boxes in B and C show the extent of the microstructure sketches portrayed in D and E, respectively.